Public procurement and supplier job creation: Insights from auctions - Stjepan Srhoj; Melko Dragojević (Global Labor Organization (GLO), 2021)
Public procurement contracts (PPCs) of goods, services and works is about one tenth of global gross domestic product. Much research has been conducted on government spending and its aggregate effects, but evidence is scarce at the micro-level. This study exploits sealed-bid PPC auctions of construction works, discontinuity in bidders' win margin and firms' daily employment variation to provide a causal estimate of winning a PPC on firms' employment. Winning a PPC has a small positive impact on a firm's short-run employment. The study investigates mechanisms and heterogeneity that can explain the initial small magnitudes. No compelling evidence is found in favour of political connections, an information leakage channel or PPC size as explanations for the small magnitude. A investigation of longer period shows the impact phases out in less than a year. The lack of a long-term impact is due to runners-up winning more PPCs and runners-up substituting towards more market revenue in the year after closely losing a PPC. Finally, the impacts are concentrated in construction firms that conduct the majority of contracted work in-house. The final estimation shows the effect is about four new employees per PPC with a public cost per job created at exteuro45,200 [ exteuro34,200 - exteuro66,200].
Keywords: H57; D44; D22; M51; 330; public procurement; auction; firms; jobs; employment